Arabic Calligraffiti: A Political Liminal Practice in Street Art’s Visual Scene - Zahar, Hela (Street Art & Urban Creativity, 2022)
Arabic calligraffiti, a form of urban art, has spread in both Arab and Western cities, including Montreal, Paris and cities in Tunisia and elsewhere in the Arabic world. Its visibility underlines different tensions and highlights various conflicts and power relations, such as Arab-Western tensions in the visual culture of Western cities, tensions around the religious role of Islamic calligraphy in Arab cities, tensions around urban art in all cities, and tensions around the various digital spaces where these works are disseminated (Zahar, 2018). Arabic calligraffiti has its origins in Islamic calligraphy, modern Arabic calligraphy and the globalized graffiti movement. It is situated at the problematic meeting of the Arab and Western worlds and raises the question of possible interpenetrations and/or tensions (physical and digital) between those two cultural ensembles. Arabic calligraffiti can be considered in many ways as a liminal practice. In this article, we will illustrate the different facets of this liminal practice.